Implementasi Pendidikan Karakter Gotong Royong dan Peduli Sosial Masyarakat: (Studi Kasus pada Pembangunan Mushola Nurul Hidayah di Kelurahan Purwosari Kecamatan Metro Utara Kota Metro) - Ehwanudin Ehwanudin; Mispani Mispani (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2018)
This study aims to describe the implementation of mutual assistance character education and social care for the community in the construction of the Nurul Hidayah mosque in Purwosari Village, Metro North Subdistrict, Metro City. The data source of this research is the resource person or informant and some literature related to the subject matter of the discussion. The data collection technique uses observation, documentation and interview instruments. While the data analysis techniques use interactive models through the process of collecting data, reducing data, presenting data and drawing conclusions. From the results of this study, it can be concluded that the implementation of mutual cooperation character education and social care for the construction of Nurul Hidayah prayer room in Purwosari Village Metro Metro Subdistrict, Metro City, based on mutual cooperation indicators shows that people have good willingness to cooperate and are not selfish. Whereas based on social care indicators show that the community in devotional work can treat other people politely and politely, want to listen to others and not demean others.